Predictors of oral health‐related quality of life in Iranian adolescents: A prospective study. Issue 1 (6th April 2017) - Pakpour, Amir H.; Lin, Chung‐Ying; Kumar, Santhosh; Fridlund, Bengt; Jansson, Henrik
Abstract: Aim: In the present study, we evaluated the direct and mediating (indirect) effects of clinical oral conditions, dental anxiety, sense of coherence (SOC), and socioeconomic variables on oral health‐related quality of life (OHRQoL) and general health‐related quality of life (GHRQoL) in Iranian adolescents. Methods: A longitudinal design was used with a sample of 1052 (694 males, mean age=15.05 years) schoolchildren from Qazvin, Iran. Each participant completed a background information sheet and the following scales at baseline: Modified Dental Anxiety Scale, SOC, PedsQL 4.0 Generic Core Scale, and PedsQL Oral Health Scale. The PedsQL 4.0 Generic Core and Oral Health scales were recompleted at the 18‐mo follow up. Results: Father's education, monthly family income, dental anxiety, Community Periodontal Index (CPI), decayed, missing, and filled teeth (DMFT), and SOC significantly and directly predicted OHRQoL at 18 mo. Father's education had indirect effects on OHRQoL through CPI and DMFT, family income had indirect effects through DMFT, and dental anxiety had indirect effects through CPI. OHRQoL at 18 mo (β=0.499) and SOC (β=0.084) had significant and direct and mediating effects through OHRQoL on GHRQoL, while father's education, monthly family income, dental anxiety, CPI, and DMFT only showed mediating effects. Conclusions: Clinical oral indicators had direct effects on OHRQoL, but mediated the effects of dental anxiety and socioeconomic status on both OHRQoL and GHRQoL.